Change vegetation cover using some plant indicators and indicators to monitor desertification: (Karma / Anbar province - applied study) - Al-Fahdawi, Taha Ahmed Abed Abtaan (Al-Adab Journal, 2019)
The problem of desertification is one of the most important contemporary environmental problems. The continued depletion of vegetation cover intensifies the degradation and productivity of agricultural land due to neglect, salinization, misuse and management, and thus the emergence of desertification and drought.The study area (Karma district) located west of the capital Baghdad, one of the important agricultural sites in the country, the study included changing vegetation cover using vegetation evidence by relying on the analysis of three visuals of the winter season of the satellite Landsat on different dates, (ETM +) on 06/11/2010, and two satellites for the satellite Landsat 8 with the sensor (OLI) on (21/10/2013) and (22/11/2017).The study examined the relationship between seven plant evidence: Normalized Difference Vegetation Index (NDVI), Vegetation Index Difference (DVI), Ratio Simple Index (SRI) , Ratio Vegetation Index (RVI) , Moisture Stress Index (MSI) , Soil Adjusted and Vegetation Index (SAVI) and Difference Renormalized Vegetation Index (RDVI) , by calculating the spectral reflectivity values ​​at different wavelengths, the best results were found by applying the NDVI, SAVI and RDVI indices in the study of vegetation density and soil degradation status, As it represented a positive relationship at the wavelength of nearby infrared radiation